2008
DOI: 10.1080/10915810802550835
|View full text |Cite
|
Sign up to set email alerts
|

Final Report on the Safety Assessment of Trichloroethane

Abstract: Trichloroethane functions in cosmetics as a solvent. Although Trichloroethane has been reported to the Food and Drug Administration (FDA) to be used in cosmetic products, an industry survey found that it is not in current use in the cosmetic industry. Trichloroethane is considered a Class I ozone-depleting substance by the Environmental Protection Agency (EPA) and its use is prohibited in the United States, unless considered essential. The FDA has stated that Trichloroethane's use in cosmetics is considered no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The use of myristic acid as the substrates also has few advantages: its usage is FDAapproved and is also declared GRAS clear by FEMA. 18,19 Our studies also showed that the optimized method of MASL production had no adverse effect on the cell mass (refer Figure 2). The probable reason for successful synthesis of this SL is its role in myristoylation: a lipid modification involving the addition of myristic acid to the N terminal of glycine.…”
Section: ■ Results and Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The use of myristic acid as the substrates also has few advantages: its usage is FDAapproved and is also declared GRAS clear by FEMA. 18,19 Our studies also showed that the optimized method of MASL production had no adverse effect on the cell mass (refer Figure 2). The probable reason for successful synthesis of this SL is its role in myristoylation: a lipid modification involving the addition of myristic acid to the N terminal of glycine.…”
Section: ■ Results and Discussionsupporting
confidence: 57%
“…It can thus be concluded that the resting cell method along with induction works best for synthesis of the short-chain derived SL–MASL (refer Figure ). The use of myristic acid as the substrates also has few advantages: its usage is FDA-approved and is also declared GRAS clear by FEMA. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…In support of this notion, an overlap in skin and irritation of the airways is seen in a range of substances in both humans and animals. These include the following: acetaldehyde plastics, acetic acid, acid anhydrides, acrolein plastics, ammonia fertilisers, methyl bromide, calcium hydroxide, chloroacetophenone, formaldehyde, hydrochloric acid, hydrofluoric acid, isocyanates, mercury, osmium tetroxide, phosgene, sulphuric acid, phosphoric acid aerosol, perchlorethylene, polyurethane foam, mono‐, di‐, and triethanolamine, formic acid, hydrogen peroxide, sodium hydroxide and sodium hypochlorite (Andersen & Maibach, 1995 ; Blain, 2003 ; Boulet, 1988 ; Czerwinska‐Dihm & Rudzki, 1981 ; Dahlin et al, 2013 ; Division of Diet, Disease Prevention and Toxicology, National Food Institute, 2021 ; Ernstgård et al, 2012 ; Harris et al, 1981 ; Hooker, 2008 ; Kieć‐Świerczyńska et al, 2014 ; Kishi et al, 1991 ; Knaak et al, 1997 ; Larsen, 2001 ; I Makarovsky et al, 2007 ; Makarovsky et al, 2008 ; Nielsen, 2018 ; Nowak, 2002 ; Plavec et al, 1993 ; Preisser et al, 2011 ; Roudabush et al, 1965 ; Rubin et al, 1992 ; Sekizawa et al, 1994 ; Slaughter et al, 2019 ; Tewari‐Singh et al, 2017 ; Tovar & Leikin, 2015 ; Yelon et al, 1996 ).…”
Section: Methodsmentioning
confidence: 99%
“…"Basiscreme DAC" is a pharmaceutical cream commonly used in humans and generally considered safe. However, it consists of, among others things, propylene glycol, cetyl alcohol, and glyceryl stearate, ingredients which have been demonstrated to induce mild skin irritations in animals such as mice and rabbits, partially even in lower doses than the ones in "Basiscreme DAC" (Johnson, 1988(Johnson, , 2004Johnson et al, 2012). Furthermore, it has been demonstrated that an experimental acanthosis can be induced in guinea pigs after a seven-day treatment with yellow petrolatum (Born, 1969).…”
Section: Cervical Skinmentioning
confidence: 99%